Pengembangan Soal Higher Order Thingking Skill (HOTS) pada Mata Pelajaran Sejarah di SMA - Intan Gustiana Mildasari; Aisiah Aisiah (Jurnal Kronologi, 2022)
Abstract This research is motivated by the fact that HOTS-based questions have not been found in the assessment of history learning outcomes at SMA Negeri 1 Kerinci. The objectives of this study include: 1) formulating steps for developing HOTS-based questions in high school history subjects, 2) testing the feasibility of HOTS-based history learning outcomes assessment questions in high school, 3) testing the practicality of HOTS-based history learning outcomes assessment questions in high school. This research uses development research method by following the steps of ADDIE model development. Data collection uses a collection instrument in the form of a validation sheet. The subject of product feasibility testing involves historians and evaluation experts. The product practicality test involved one history teacher and 20 students at SMA Negeri 1 Kerinci. The data analysis technique used quantitative and qualitative approaches. The results of the product feasibility test in terms of material by Indonesian historical material experts were obtained with high category validity with a score of 0.86 with a mean score of 3.85 (very feasible). The results of the product feasibility test by the evaluation expert were obtained with high category validity with a score of 0.87 with a mean score of 3.63 (very feasible). The results of the product practicality test by the teacher obtained an average score of 3.8 (very practical) and by students an average score of 3.86 (very practical). Thus, the HOTS-based historical learning outcome assessment instrument is feasible and practical to use for high school students. Keywords: Higher Order Thingking Skill (HOTS), historical learning Abstrak Penelitian ini dilatarbelakangi oleh belum ditemukannya soal berbasis HOTS pada penilaian hasil belajar sejarah di SMA Negeri 1 Kerinci. Tujuan penelitian ini antara lain: 1) merumuskan langkah-langkah pengembangan soal berbasis HOTS pada mata pelajaran sejarah SMA, 2) menguji kelayakan soal penilaian hasil belajar sejarah berbasis HOTS di SMA, 3) menguji kepraktisan soal penilaian hasil belajar sejarah berbasis HOTS di SMA. Penelitian ini menggunakan metode penelitian pengembangan dengan mengikuti langkah pengembangan model ADDIE. Pengumulan data menggunakan instrumen pengumpulan berupa lembar validasi. Subjek uji kelayakan produk melibatkan ahli sejarah dan ahli evaluasi. Uji praktikalitas produk melibatkan satu orang guru sejarah dan 20 peserta didik di SMA Negeri 1 Kerinci. Teknik analisis data menggunakan pendekatan kuantitatif dan kualitatif. Hasil uji kelayakan produk dari segi materi oleh ahli materi sejarah Indonesia diperoleh dengan validitas kategori tinggi dengan skor 0,86 rerata skor 3.85 (sangat layak). Hasil uji kelayakan produk oleh ahli evaluasi diperoleh dengan validitas kategori tinggi dengan skor 0,87 rerata skor 3.63 (sangat layak). Hasil uji praktikalitas produk oleh guru diperoleh rerata skor 3.8 (sangat praktis) dan oleh peserta didik diperoleh rerata skor 3.86 (sangat praktis). Dengan demikian, instrumen penilaian hasil belajar sejarah berbasis HOTS ini layak dan praktis digunakan unutk peserta didik SMA. Kata Kunci: Higher Order Thingking Skill (HOTS), Pembelajaran Sejarah